How to improve your questioning techniques - Association for Supervision and Curriculum Development (Alexandria, VA : Association for Supervision and Curriculum Development, 2000)
This is a videotape that explores the different types of questions used in classrooms and the techniques teachers use to engage their students. Classroom teachers provide real examples of how to make every question important and challenging for students, how to frame questions to improve student learning, how to effectively follow up on student responses and how to involve students so they ask their own questions
For the classroom teacher
Keywords: Teachers -- Training; Teachers; Motion picture in teacher training